(untitled) (Research, Society and Development, 2022)
This article addresses the irresponsible self-medication of paracetamol, pointing out in a very salutary way how eventually a very common and apparently harmless practice such as self-medication of a commonly used drug can actually present serious health risks. Although the spectrum of drugs used without a medical prescription is wide, we will stick to mentioning only paracetamol. The purpose of this research is to warn about the seriousness of the dangers involved in this common practice. It is noticed that the immediate relief of pain or fever without proper professional follow-up can cause serious problems because the indiscriminate use of this medicine can mask other diseases or even cause drug intoxication.